Perancangan Antarmuka Sistem Informasi Akademik Siswa berbasis Web menggunakan Metode Human Centered Design (Studi Kasus: SMK Negeri 8 Malang) - Anis Wardlatul Ulfa Wahidah; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SMK Negeri 8 Malang is an institution engaged in the field of education in the city of Malang. SMK Negeri 8 Malang is a state-owned and accredited A and has implemented the Revised 2013 curriculum in teaching and learning activities. Submission of academic information such as information on lesson schedules, registration, and the results of the recap of student scores is done manually. This makes students and their guardians unable to measure the development of students' abilities optimally because the results of the recap of students' scores can be seen at the end of the semester. Based on the existing problems, SMK Negeri 8 Malang requires an academic information system interface design. The interface design aims to provide an overview of the application of student academic information systems and improve the efficiency of management and presentation of information for students at SMK Negeri 8 Malang. The interface design that will be used as a solution in this study uses the Human-Centered Design (HCD) method. The result of this research is a high fidelity prototype design which was evaluated by 8 respondents using the System Usability Scale (SUS) questionnaire. The test results using the SUS questionnaire obtained an average SUS score of 75.31 which can be categorized as feasible or acceptable by users.